Recent methods for the synthesis of α-acyloxy ketones - Prasad, P. K.; Reddi, R. N.; Arumugam, S. (Organic and biomolecular chemistry, 2018)
The present review provides a broad description of the methods reported for the synthesis of α-acyloxy ketones and some of their derivatives. α-Acyloxy ketones and their derivatives are vital synthetic intermediates and are ubiquitous as biochemical constituents of living organisms, biologically active natural products and pharmaceuticals. Due to their biological importance, new methods for their synthesis are being continuously developed and documented in the recent past. However, the chemical literature lacks a comprehensive summary on the synthetic methodologies targeting α-acyloxy ketones. In an attempt to fill this void, this review discusses their synthetic procedures developed over time. The synthetic approaches are systematically classified based on the substrates used. The mechanistic details for certain critical cases are also discussed. In the past, preparation of α-acyloxy ketones was reported from functionalized ketones like α-haloketones and diazo esters. Later on, among the reactions that formed the acyloxy ketones, oxidative coupling of ketones with carboxylic acids both under metal and metal-free conditions made their synthesis simple and versatile. Specifically, in the last decade, many oxidative coupling reactions emerged as a powerful tool for the synthesis of α-acyloxy ketones. Quite recently, acyloxy ketones’ synthesis has been reported from commercially available alkenes and alkynes through oxidative addition reactions. Subsequently, the mechanistic details for these coupling reactions became interesting to many organic chemists. The asymmetric version of the title compounds hails from their enzymatic resolution to metal catalysed chiral synthesis. Besides, the synthesis of acyloxy ketones from epoxides, alcohols and enamides using various oxidative reagents has also been documented.